Language barriers in hotels How language proficiency influences perceived service quality - Wagner, Joshua (Student Undergraduate Research E-journal!, 2018)
In the hotel industry, which is highly international and therefore prone to language barriers, the interaction between an employee and a guest is very important as companies try to make them loyal to their brand and reap the benefits of guest retention. In this research, an experiment has been conducted to test the relationship between language proficiency (LP) and perceived service quality (PSQ). In a nutshell, a B2 level (Common European Framework of Reference, Council of Europe, 2001) emerged as the minimum requirement to perform above average and statistical analysis revealed that different indicators of PSQ are affected differently by a lack of LP.